Inhibitory Effect of β-Sitosterol on TNBS-Induced Colitis in Mice - Lee, In-Ah; Kim, Eun-Jin; Kim, Dong-Hyun (Planta Medica, 2012)
β-Sitosterol, a common sterol in herbal medicines, exhibits anti-inflammatory effects beneficial in the treatment of lung inflammation, asthma, and bronchospasm. To evaluate whether β-sitosterol also has anticolitic benefits, we tested the effect of β-sitosterol on 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis in mice. β-Sitosterol inhibited colon shortening and led to lowered macroscopic scores and myeloperoxidase activity in TNBS-treated colitic mice. β-Sitosterol also inhibited the expression of proinflammatory cytokines TNF-α, IL-1β, and IL-6, and an inflammatory enzyme, cyclooxygenase (COX)-2, in the colons of TNBS-induced colitic mice, as well as the activation of NF-κB. Based on these findings, β-sitosterol may ameliorate colitis by inhibiting the NF-κB pathway.
Keywords: β-sitosterol; inflammation; colitis; NF-κB pathway